Prognostic analysis of telangiectatic osteosarcoma of the extremities - Zhong, Wei; Luo, Wei; Lin, Zili; Wu, Ziyi; Yuan, Yuhao; He, Yizhe (Frontiers in Oncology, 2023)
Background and Objectives: Telangiectatic osteosarcoma (TOS) is a rare but highly malignant subtype of osteosarcoma. Although surgical treatment is the primary treatment modality for osteosarcoma, evidence on the benefits of different surgical methods in patients with TOS is lacking. This study aimed to compare the effects of different surgical and adjuvant treatments on overall survival of TOS, and the association of patient demographics, oncological characteristics, and socioeconomic status on treatment outcomes. Method: This retrospective study selected the most common TOS cases of the extremities registered in the Surveillance, Epidemiology, and End Results database from 1989 to 2019. Univariate and multivariate Cox regression models were used to analyze all prognostic factors, and Kaplan-Meier analyses were performed for disease-specific treatment factors of survival. Result: A total of 127 patients were included in the analysis. The average age at initial diagnosis was 20.09 years. In univariate analyses, the absence of metastasis at initial diagnosis, limb-salvage surgery, adjuvant chemotherapy, and regional lymph node dissection were associated with a lower risk of death. Multivariate analysis further showed that the presence or absence of distant metastasis and regional lymph node dissection, implementation of adjuvant chemotherapy, and choice of surgical method were independent predictors of prognosis. Conclusion: Distant metastasis and regional lymph node dissection are associated with poorer outcomes in TOS. Limb salvage is associated with better prognoses, and there is no clear benefit of conventional chemotherapy over neoadjuvant chemotherapy.